Nationalism - Kedourie, Elie. (Oxford, UK ; Cambridge, Mass., USA : Blackwell, 1960)
Traces the philosophical foundations of nationalist doctrine, the conditions which gave rise to it and the political consequences of its spread in Europe and elsewhere in the 19th and 20th centuries. This edition contains a new introduction by the author.
Politics in a new style -- Self-determination -- State and individual -- The excellence of diversity -- National self-determination -- Nationalism and politics: I -- Nationalism and politics: II.
Includes bibliographical references and index.
Keywords: Nationalism